2021
DOI: 10.3389/fimmu.2021.618807
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic-di-GMP Induces STING-Dependent ILC2 to ILC1 Shift During Innate Type 2 Lung Inflammation

Abstract: Type 2 inflammation is found in most forms of asthma, which may co-exist with recurrent viral infections, bacterial colonization, and host cell death. These processes drive the accumulation of intracellular cyclic-di-nucleotides such as cyclic-di-GMP (CDG). Group 2 innate lymphoid cells (ILC2s) are critical drivers of type 2 lung inflammation during fungal allergen exposure in mice; however, it is unclear how CDG regulates lung ILC responses during lung inflammation. Here, we show that intranasal CDG induced e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…While the role of ILC1s in asthma remains largely unknown, ILC3s are elevated in severe asthma and IL-17 producing ILC3s were required for increased airway resistance in a mouse model of obesity-induced asthma ( 60 ). A recent report demonstrated that administration of the universal bacterial second messenger, cyclic di-GMP, skewed the response to AA from ILC2s to IFNγ-producing ILC1s ( 61 ). Therefore, it is plausible that exposure to AA in the presence of CFA may cause a shift favoring ILC1 and ILC3s in the lung microenvironment along with Th1 and Th17 cells.…”
Section: Discussionmentioning
confidence: 99%
“…While the role of ILC1s in asthma remains largely unknown, ILC3s are elevated in severe asthma and IL-17 producing ILC3s were required for increased airway resistance in a mouse model of obesity-induced asthma ( 60 ). A recent report demonstrated that administration of the universal bacterial second messenger, cyclic di-GMP, skewed the response to AA from ILC2s to IFNγ-producing ILC1s ( 61 ). Therefore, it is plausible that exposure to AA in the presence of CFA may cause a shift favoring ILC1 and ILC3s in the lung microenvironment along with Th1 and Th17 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The relevance of innate lymphocytes such as ILC1s may be more apparent in the advent of zoonoses as has recently occurred in the SARS‐CoV‐2 pandemic. [ 100 , 101 ]. Thus, in instances where immunological memory is absent, ILC1s may serve as first‐line responders to curb viral spread and alert other immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, STING represses IL-13-induced STAT6 phosphorylation in subjects with rhinosinusitis by increasing expression of the STAT6 inhibitor SOCS1 (suppressor of cytokine signaling 1) ( Figure 3 ) ( 144 ). SOS1 induction may also underlie the observation that STING signaling in ILC2s promotes a phenotypic shift to Type 1 ILC (ILC1) during lung inflammation ( 145 ). Taken together, these studies suggest that the role of STING in type 2 immunity is complex and context dependent.…”
Section: Part 2: the Role Of Autoinflammation In Type 2 Immune Responsesmentioning
confidence: 99%